Effect Of Solar Radiation On Module Photovoltaics 100 Wp With Variation of Module Slope Angle - Azriyenni Azhari Zakri; Iswadi Hasyim Rosma; Dohardo P H Simanullang (IAES Indonesian Section, 2018)
Solar photovoltaic generation system is a very promising type of renewable energy, particularly when it is implemented in the tropical country like Indonesia where it receives a huge amount of sunshine. Solar photovoltaic generation system can be utilised to supply power for different types of consumer, namely utility grids, industrials as well as household. This article discusses the effect solar radiation to the photovoltaic module with different slope angles namely; 300, 400 and 500 respectively. It was used a 100 Wp solar module in the research. It is not only the slope angle of module analysed in this article but also the weather condition such as: sunny or cloudy conditions. The performances of solar photovoltaic at temperature ranging from 280C to 500C are analysed significantly. The results showed that the above conditions affected the voltage generated by solar photovoltaic system. Finally, the results of this test will be compared with the simulation results of photovoltaic system modeling using Matlab/Simulink.